Fluorescent Nanodiamond–Nanogels for Nanoscale Sensing and Photodynamic Applications. Issue 7 (9th July 2021) - Wu, Yingke; Alam, Md Noor A; Balasubramanian, Priyadharshini; Winterwerber, Pia; Ermakova, Anna; Müller, Michael; Wagner, Manfred; Jelezko, Fedor; Raabe, Marco; Weil, Tanja
Abstract : Nanoscale Sensing In article number 2000101, Fedor Jelezko, Marco Raabe, Tanja Weil, and co‐workers establish "adsorption‐crosslinking" as new concept to modify nanodiamond surfaces and stabilize them within a crosslinked polymeric nanogel shell. The coated nanodiamonds are internalized into cells thus allowing nanoscale sensing applications. The nanodiamond‐nanogels are able to detect paramagnetic ions and magnetic proteins. Moreover, they could be useful for photodynamic applications in combination with ruthenium complexes.